Renal dialysis, diabetes and iugr: delivery and peripartum care. (18th April 2012) - Simpson, P; Turnbull, H; McKelvey, A; Temple, R; Turner, J; Ross, C; Barker, L; Stanley, K
Abstract : A woman with Type I diabetes presented at 6 +0 /40 with a history of severe retinopathy, hypertension and nephropathy. A previous combined renal and pancreatic transplant had failed necessitating haemodialysis five times a week. She miscarried a DCDA twin pregnancy at 21 weeks the previous year. At 25 +6 /40 fetal ultrasound indicated growth restriction, with absent umbilical artery diastolic flow. Dexamethasone was administered. Fetal wellbeing was monitored with biophysical profiling until 27 +1 /40 when reversed flow in the Ductus Venosus A wave prompted delivery by LSCS under GA. Post-partum, the primary concern was fluid and electrolyte balance. Intra-operative haemorrhage was replaced with IV crystalloid and a return to restricted oral fluid intake was encouraged. Blood glucose was controlled with a reduced basal-bolus regime. On the first post-operative day serum potassium was 6.0 mmol/L and was corrected by haemodialysis. Daily haemodialysis continued for a week post-partum to clear excess fluid and manage worsening hypertension. Initially all antihypertensive medication was stopped but had to be re-titrated to control the blood pressure. Recovery was complicated by vomiting and ketosis secondary to basal atelectasis and pneumonia on the fourth post-operative day. This was managed with cautious fluid resuscitation and an insulin infusion. Conclusion: The challenges in this pregnancy were numerous but the peripartum fluid balance, blood sugar and thrombo-prophylaxis, are of particular interest and will be discussed. A proactive and multi-disciplinary approach to her care resulted in a live birth without significant compromise to maternal health.